Breaking the Pt electron symmetry and OH spillover towards ptir active center for performance modulation in direct ammonia fuel cell - Barik, Sidharth; Kharabe, Geeta Pandurang; Samal, Pragnya Paramita; Urkude, Rajashri R.; Kumar, Sachin; Yoyakki, Athira; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2024)
The growing interest in low-temperature direct ammonia fuel cells (DAFCs) arises from the utilization of a carbon-neutral ammonia source; however, DAFCs encounter significant electrode overpotentials due to the substantial energy barrier of the *NH2 to *NH dehydrogenation, compounded by the facile deactivation by *N on the Pt surface. In this work, a unique catalyst, Pt4Ir@AlOOH/NGr i.e., Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles controllably decorated on the pseudo-boehmite phase of AlOOH-supported nitrogen-doped reduced graphene (AlOOH/NGr) composite, synthesized via the polyol reduction method. The detailed studies on the structural and electronic properties of the catalyst by XAS and VB-XPS reveal the possible electronic modulations. The optimized Pt4Ir/ANGr composition exhibits a significantly improved onset potential and mass activity for AOR. The DFT study confirms the OHad species spillover by AlOOH and Pt4Ir (100) facilitates the conversion of the *NH2 to *NH with minimal energy barriers. Finally, testing of DAFC at the system level using a membrane electrode assembly (MEA) with Pt4Ir/ANGr as the anode catalyst, demonstrating the suitability of the catalyst for its practical applications. This study thus uncovers the potential of the Pt4Ir catalyst in synergy with ANGr, largely addressing the challenges in hydrogen transportation, storage, and safety within DAFCs. In this article, a versatile catalyst, Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles decorated on AlOOH/NGr composite. The AlOOH provides an -OH-rich surface conducive to the facile adsorption and decoration of the PtIr alloy nanoparticles and OHad species spillover from AlOOH to the Pt4Ir active center during AOR, further validating the higher experimental activity obtained in Pt4Ir/ANGr. image
Keywords: ammonia oxidation reaction (AOR); d-band center; density functional theory (DFT) study; direct ammonia fuel cells; hydroxyl spillover effect; XAS analysis

Binderless low silica X zeolite for methane separation from binary CO2/CH4 biogas stream: A comprehensive experimental and computational study - Yadav, Tushar R.; Shrotri, Aadesh R.; Kate, Pranjali N.; Devasia, George; Niphadkar, Prashant S.; Mali, Nilesh A.; Krishnamurty, Sailaja; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2025)
This study presents the synthesis of binderless Na-LSX (B-Na-LSX) and binderless NaK-LSX (B-NaK-LSX). XRD, SEM, EDS, and N-2 physisorption were used for characterization of samples. Computational modelling of prepared sorbent was performed for the fundamental understanding of zeolite topology and adsorption behaviour. The breakthrough experiments are used to evaluate the adsorption capacities on CO2/CH4 (40/60 vol%) binary biogas stream. The results were compared with commercial Na-LSX (C-Na-LSX). The breakthrough adsorption capacity of B-Na-LSX was 3.08 mmol g(-1) and 0.29 mmol g(-1) of CO2 and CH4, respectively, at 300 K and 1 bar. CO2 sorption capacity of B-Na-LSX was similar to 11 % and similar to 17 % higher than B-NaK-LSX (2.77 mmol g(-1)) and C-Na-LSX (2.56 mmol g(-1)), respectively. DFT study reveals that the higher adsorption of CO2 over CH4 was attributed to higher charge transfer from CO2 to zeolite framework. Dual-bed six-step Pressure Swing Adsorption (PSA) was performed on B-Na-LSX at 6 bar. similar to 232 cycles were run with above 98 % of CH4 purity and similar to 74 % of recovery. The life-cycle test of sorbent was studied. It was implied that the designed sorbent is effective to produce the high purity of CH4 and can be utilized for a longer period for CH4 production.
Keywords: Binderless; Biogas; LSX zeolite; methane; PSA; Separation

Boosting the CO2 reduction activity of Cu double-atom catalysts through coordination environment engineering - Amin, Seerat; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Sustainable Energy & Fuels, 2025)
Double-atom catalysts (DACs) offer a reasonable and scalable route towards carbon neutrality owing to their efficient catalytic features. However, the challenges associated with the flexibility of their coordination structure usually restrict their full potential as efficient catalysts. Herein, we comprehensively examined the impact of coordination environment regulation on the CO2R activity of Cu2-DACs supported on C, N, or B co-doped graphene using ab initio simulations. We highlighted the marked role of the local coordination sphere of Cu2-DACs in modulating their structural stability and charge transfer characteristics, thereby regulating the adsorption of CO2 and various reaction characteristics. Notably, boron- and carbon-coordinated Cu2 centres (Cu2-BxCy) resulted in remarkably strong CO2 adsorption (-0.65 to -2.31 eV), attributed to their amplified electronic interactions with the CO2 molecule. The weak CO2 binding observed on the carbon-nitrogen- and nitrogen-boron-coordinated Cu2 centres (Cu2-NxCy and Cu2-NxBy) further highlighted the role of the coordination environment in facilitating the versatile binding modes of the key reaction species. The varying CO2 interactions in these systems were further comprehended and supported by a multilevel descriptor () combining both geometric and electronic parameters. This descriptor closely mirrored the DFT results, thereby accentuating its effectiveness as a predictive tool to perfectly model the CO2 interactions on these catalysts. Moreover, the dynamic behaviour in the adsorption modes led to partial breakdown of the conventional linear scaling relations between the key CO2 reduction intermediates (*COOH, *CO, and *HCO). Among the numerous types of investigated electrocatalysts, Cu2-B5C1 emerged as a highly active and selective catalyst for methanol production, with a remarkably low limiting potential of -0.54 V, surpassing the performance of several reported Cu-based systems. Besides, our findings underscored the often-overlooked yet crucial role of explicit solvation, which significantly altered both the potential-determining step and product selectivity. These outcomes emphasized the necessity of including solvation effects in realistic electrochemical modelling. Collectively, this study provides a critical mechanistic insight into better understanding the coordination effect on the CO2R and a robust design strategy for next-generation Cu-based DACs, guiding the development of highly efficient and selective catalysts for CO2 electroreduction.